Maintaining soil fertility - Webb, William Allen (My University, 1904)
Introduction: Having lived for a number of years upon a southern Kansas wheat farm and observed the steady decrease in the productive power of the land, the writer has been interested in investigating practical methods by which this loss might be prevented and the soil maintained in a high state of productivity. For years, many farms in the Kansas wheat belt have been sown continuously in wheat. This means that every year with a crop of twenty bushels, there have been removed from each acre of such farms, thirty-five pounds of nitrogen twenty pounds of phosphoric acid and thirty-five pounds of potash.Only in rare cases have any fertilizing materials...
Citation: Webb, William Allen. Maintaining soil fertility. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Soil Fertility; Soils; Agricultural Science; Farming Techniques; Theses; Manuscripts (documents)